TEACHERSâ€™ POTENTIALS ON BECOMING PROFESSIONAL COACHES - Pratama, Hendi; Formen, Ali (Lembaran Ilmu Kependidikan, 2013)
Artikel ini berfokus pada bagaimana pengajar bahasa mempunyai potensi untuk menjadi guru professional ketika mereka diberi kesempatan dan memahami konsep professional coaching. Data penelitian didapatkan dari sebuah studi kasus yang diperoleh peneliti dari sebuah perusahaan BUMN ketika mereka melatih perusahaan tersebut, melalui sebuah program terstruktur dengan menggunakan konsep pembentuan coaching team dan pribadi yang professional. Penelitian ini diharapkan bisa membantu para guru dari latar belakang bahasa maupun disiplin ilmu yang lain untuk mengadopsi siklus pembelajaran professional untuk memperbaiki performa pengajaran mereka dikelas maupun diluar kelas.Â This paper will focus on how language teachers have the potentials to smoothly transform into professional coaches when they are given the right opportunity and understand the concepts of professional coaching. The data of the research are collected from a case study conducted by the researchers while they coached a team from an Indonesian State Company through a structured program using the concepts of personal and team development coaching. The study is expected to help teachers from language teaching background (or any other fields) to adopt professional coaching cycles to improve their teaching performance inside and outside the classrooms.Â